GATEKEEPERS AND ENVOYS: THE KHIVA KHANATE AND THE RUSSIAN EMPIRE UNDER MUHAMMAD RAHIMKHAN I (1806–1825) - Saparbaev Bunyod Khurrambek ogli (Western European Studies, 2026)
This article analyzes the nature and dynamics of relations between the Khiva Khanate and the Russian Empire during the reign of Muhammad Rahimkhan I (1806–1825), a formative yet understudied period preceding Russia’s full-scale imperial expansion into Central Asia. Drawing upon Russian diplomatic correspondence, travel accounts, Khivan chancery documents, British imperial archival materials, and modern international scholarship, the study argues that bilateral relations were shaped by pragmatic calculation rather than ideological confrontation. Trade interests, intelligence gathering, and the problem of captivity formed the core axes of interaction, while diplomacy functioned as a flexible tool adapted to shifting regional realities. The article emphasizes the agency of the Khivan elite and demonstrates that early nineteenth-century imperial interaction was characterized by incremental entanglement rather than direct domination. The findings contribute to a more nuanced understanding of precolonial Eurasian diplomacy and challenge linear narratives of imperial expansion.
Keywords: Khiva Khanate; Russian Empire; Muhammad Rahimkhan I